2022
DOI: 10.1002/ajb2.16099
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizae influence plant vegetative and floral traits and intraspecific trait variation

Abstract: Premise: Arbuscular mycorrhizal fungi (AMF) can strongly influence host plant vegetative growth, but less is known about AMF effects on other plant traits, the relative impacts of AMF on vegetative growth versus floral traits, or AMF-induced intraspecific variation in traits. Methods: In an experimental greenhouse study, we inoculated seven species of wildflowers with six species of AMF in a factorial design. We assessed how the AMF-forb combinations influenced plant survival, vegetative biomass, and floral tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
(69 reference statements)
1
3
0
Order By: Relevance
“…Other studies considering C. madagascariensis have reported that this IAPS may improve soil fertility as described in the “island of fertility” hypothesis [1, 29]. Our results agree with two previous hypotheses about: (i) “changed‐habitat” as influenced by the biological invasion promoted by C. madagascariensis [5]; and (i) “plant‐host pairing specificity” since we have found exclusive AMF species for both studied ecosystems [7, 8, 31]. According to the study done by Souza et al [5], C. madagascariensis tends to promote the abundance of Claroideoglomus , Funneliformis , and Rhizoglomus in their rhizosphere.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies considering C. madagascariensis have reported that this IAPS may improve soil fertility as described in the “island of fertility” hypothesis [1, 29]. Our results agree with two previous hypotheses about: (i) “changed‐habitat” as influenced by the biological invasion promoted by C. madagascariensis [5]; and (i) “plant‐host pairing specificity” since we have found exclusive AMF species for both studied ecosystems [7, 8, 31]. According to the study done by Souza et al [5], C. madagascariensis tends to promote the abundance of Claroideoglomus , Funneliformis , and Rhizoglomus in their rhizosphere.…”
Section: Discussionsupporting
confidence: 91%
“…Of course, notions and vocabulary that betray unacceptable and, indeed, “unscientific” preconceptions, implications, or conclusions (e.g., in the domain of eugenics), should very much be rejected—but I do not think that “gender” in plants is one of them. In continuing to use gender as a useful notion in studying plant reproductive strategies, it would still pay to be sensitive to the potential obstacles for understanding that resonance with societal use might pose (Oberle and Fairchild, 2023).…”
Section: Sex Roles and Gender In Botany And Society: Do We Need A New...mentioning
confidence: 99%
“…Ironically, in apparent “sympathy with the ideas and goals of feminism” (Haig, 2000), biologists have increasingly used the word gender as a simple synonym for sex . This trend has been criticized, with the suggestion that we desist from using gender in the specific context of plant sexuality, both in deference to the feminist cause and because the word has come to have meanings that might compromise our communication and teaching (Oberle and Fairchild, 2023).…”
Section: Sex Roles and Gender In Botany And Society: Do We Need A New...mentioning
confidence: 99%
“…The “On the Nature of Things” (“OTNOT”) essay by Oberle and Fairchild (2023) provides a brief history of the uses of the term gender in the botanical literature, which emphasize the continuous nature of sporophyte sexual function, and its uses in the social sciences, which view gender as a classification of human individuals determined by self‐identity, experience, and social context. They argue that use of the term gender in reference to plants should be avoided and that, in particular, instruction in the biological sciences should aim for inclusive language.…”
mentioning
confidence: 99%